An organic-inorganic hybrid material for removing heavy metal ions in sewage and a preparation method thereof

By designing a ternary composite structure of sulfonated polyethersulfone/ZIF-8/MnFe2O4, the problems of selectivity and separation difficulties of existing adsorption materials for various heavy metal ions are solved, achieving efficient, easy-to-separate, and low-cost heavy metal removal.

CN121063635BActive Publication Date: 2026-01-23DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511616767.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-23
Estimated Expiration
2045-11-06

AI Technical Summary

Technical Problem

Existing adsorption materials have low selectivity and efficiency in removing heavy metal ions other than lead, such as cadmium, copper, and zinc, from wastewater. They are difficult to separate, have poor regeneration performance, are cumbersome to operate, are prone to secondary pollution, and are costly.

Method used

By employing a ternary composite structure of sulfonated polyethersulfone/ZIF-8/MnFe2O4, combining electrostatic adsorption, coordination complexation and physical adsorption mechanisms, magnetic components of manganese ferrite nanoparticles are introduced, and thiol coordination sites are provided through L-cysteine ​​functionalization, forming an efficient and easily separable organic-inorganic hybrid material.

Benefits of technology

It achieves highly efficient and selective adsorption of various heavy metal ions, simplifies the separation process, reduces the risk of secondary pollution, and significantly reduces usage costs through regeneration with acidic solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 10000249980157
    Figure 10000249980157
Patent Text Reader

Abstract

The present application relates to the technical field of water treatment materials, and particularly relates to an organic-inorganic hybrid material for removing heavy metal ions in sewage and a preparation method thereof, the material is composed of the following components in mass percentage: sulfonated polyether sulfone, content is 30-40%; ZIF-8 metal organic framework material, content is 30-45%; cysteine functionalized manganese ferrite nanoparticles, content is 20-30%, the present application adopts a sulfonated polyether sulfone / ZIF-8 / MnFe2O4 ternary composite structure, integrates three mechanisms of electrostatic adsorption, coordination complexation and physical adsorption, and improves the adsorption capacity and selectivity for various heavy metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment materials technology, and in particular to an organic-inorganic hybrid material for removing heavy metal ions from wastewater and its preparation method. This material can efficiently remove various heavy metal ions such as lead, cadmium, copper, and zinc from water, and has good regeneration performance and magnetic separation function. Background Technology

[0002] With rapid industrial development, heavy metal pollution has become a significant factor affecting water quality. Heavy metal ions are not only difficult to degrade but also persistent and bioaccumulative, posing serious health risks after accumulating through the food chain. Therefore, developing efficient, economical, and environmentally friendly heavy metal adsorption materials is of great importance for protecting the water environment and human health.

[0003] Currently, adsorbent materials used for the removal of heavy metals from water mainly include traditional activated carbon, ion exchange resins, and emerging nano-adsorbents. Among them, Chinese patent CN 109046292 B discloses "an organic-inorganic hybrid adsorbent with a hierarchical structure, its preparation method, and its application." This patent uses ion exchange resin as the framework, polydopamine as an adhesive, thiol protease as a guide agent, and iron as an inorganic nano-component to construct an organic-inorganic hybrid adsorbent with a sub-10nm flower-like hierarchical structure. This adsorbent exhibits good adsorption performance for lead ions.

[0004] However, the above-mentioned technical solutions still have the following shortcomings: on the one hand, the adsorbent is mainly for lead ions, and its adsorption selectivity and treatment efficiency for other heavy metal ions such as cadmium, copper, and zinc are low; on the other hand, the adsorbent needs to be separated from the water body through filtration, sedimentation and other methods after use, which is cumbersome and can easily cause secondary pollution; in addition, the regeneration performance of the adsorbent is limited, and the long-term use cost is high.

[0005] Metal-organic frameworks (MOFs), as a rapidly developing class of porous materials in recent years, have shown broad application prospects in gas storage, catalysis, and adsorption due to their high specific surface area, tunable pore structure, and abundant functional groups. In particular, ZIF-8 (2-methylimidazolium zinc) is widely used in gas separation and catalysis due to its good chemical stability and high specific surface area. However, MOF materials still face challenges in water treatment applications, such as poor dispersibility and separation difficulties.

[0006] Therefore, there is an urgent need to develop a novel organic-inorganic hybrid material that combines high-efficiency adsorption, easy separation, and good regeneration performance for the efficient removal of various heavy metal ions from water. Summary of the Invention

[0007] The purpose of this invention is to provide an organic-inorganic hybrid material for removing heavy metal ions from wastewater and its preparation method, aiming to solve the technical problems existing in the prior art, such as single adsorption selectivity, difficulty in separation, and poor regeneration performance.

[0008] To achieve the above objectives, the present invention provides an organic-inorganic hybrid material for removing heavy metal ions from wastewater, the material comprising the following components by mass percentage: sulfonated polyethersulfone, 30-40%; ZIF-8 metal-organic framework material, 30-45%; and cysteine-functionalized manganese ferrite nanoparticles, 20-30%.

[0009] Preferably, the degree of sulfonation of the sulfonated polyether sulfone is 1.5-2.5 mmol / g.

[0010] Preferably, the ZIF-8 metal-organic framework material has a specific surface area of ​​1200-1800 m² / g and an average pore size of 1.0-1.5 nm.

[0011] Preferably, the manganese ferrite nanoparticles have an average particle size of 20-50 nanometers and a saturation magnetization of 40-60 angstroms / gram.

[0012] This invention also provides a method for preparing the above-mentioned organic-inorganic hybrid material, comprising the following steps:

[0013] Step 1: Prepare sulfonated polyethersulfone;

[0014] Step 2: Synthesize ZIF-8 metal-organic framework material;

[0015] Step 3: Prepare manganese ferrite nanoparticles;

[0016] Step four: Perform L-cysteine ​​functionalization on the manganese ferrite nanoparticles;

[0017] Step 5: The sulfonated polyethersulfone, the ZIF-8 metal-organic framework material, and the cysteine-functionalized manganese ferrite nanoparticles are mixed to prepare a ternary composite material.

[0018] The preparation of sulfonated polyethersulfone in step one includes: dissolving polyethersulfone in N,N-dimethylformamide, adding a mixture of concentrated sulfuric acid and chlorosulfonic acid, reacting at 50-70°C for 4-8 hours, then pouring the reaction solution into ice water, collecting the precipitate and washing it with deionized water until neutral, and drying it under vacuum at 80°C for 24 hours.

[0019] The synthesis of ZIF-8 in step two includes: dissolving zinc nitrate hexahydrate in methanol to form a first solution, dissolving 2-methylimidazole in methanol to form a second solution, quickly pouring the first solution into the second solution, stirring at room temperature for 20-28 hours, centrifuging to separate the product, washing it three times with methanol, and drying it under vacuum at 60°C for 12 hours.

[0020] The preparation of manganese ferrite nanoparticles in step three includes: dissolving manganese nitrate tetrahydrate and ferric nitrate nonahydrate in deionized water at a molar ratio of 1:2, adding an aqueous solution containing sodium hydroxide under nitrogen protection, adding polyvinylpyrrolidone as a dispersant, heating the reaction in a water bath at 70-90℃ for 1-3 hours, separating the product by magnetic force, washing it three times each with deionized water and ethanol, and drying it under vacuum at 60℃ for 12 hours.

[0021] The L-cysteine ​​functionalization process in step four includes: dispersing the manganese ferrite nanoparticles in a phosphate buffer solution containing L-cysteine, wherein the pH of the phosphate buffer solution is 7.2-7.6; sonicating for 30 minutes; stirring at room temperature for 10-14 hours; magnetically separating the product; washing three times each with phosphate buffer and deionized water; and vacuum drying at 40°C for 12 hours.

[0022] The preparation of the ternary composite material in step five includes: dissolving the sulfonated polyethersulfone in N,N-dimethylformamide, adding the ZIF-8 metal-organic framework material and the cysteine-functionalized manganese ferrite nanoparticles, ultrasonically dispersing for 30 minutes, stirring and mixing at room temperature for 6 hours, pouring the mixture into a flat mold, drying at 70°C for 8 hours to form a composite film, soaking in deionized water for 24 hours to remove the solvent, vacuum drying at 40°C for 24 hours, pulverizing the dried composite film and screening out particles of 0.5-1.0 mm to obtain the final composite adsorbent material.

[0023] The beneficial effects of this invention are:

[0024] 1. This invention employs a ternary composite structure of sulfonated polyethersulfone / ZIF-8 / MnFe2O4, which integrates three mechanisms: electrostatic adsorption, coordination complexation, and physical adsorption, thereby improving the adsorption capacity and selectivity for various heavy metal ions.

[0025] 2. This invention introduces a manganese ferrite magnetic component, endowing the material with magnetic response properties. It can quickly separate the adsorbent by applying an external magnetic field, avoiding the drawbacks of traditional separation methods such as filtration and sedimentation, improving the ease of operation and reducing the risk of secondary pollution.

[0026] 3. This invention functionalizes magnetic components with L-cysteine, introducing thiol (-SH) coordination sites, which significantly enhances the affinity and selective adsorption capacity for heavy metal ions;

[0027] 4. The material of the present invention maintains a high heavy metal adsorption efficiency even under conditions of high concentrations of coexisting ions such as Na⁺, K⁺, Ca²⁺, and Mg²⁺, demonstrating excellent anti-interference ability.

[0028] 5. The material of this invention can be regenerated by acidic solution, and its adsorption capacity remains at a high level even after being recycled more than 5 times, which greatly reduces the cost of use. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0030] The core of this invention lies in the design of an organic-inorganic hybrid material with a ternary composite structure of sulfonated polyethersulfone / ZIF-8 / MnFe2O4. Through the synergistic effect of the three components, it achieves efficient and selective adsorption and convenient separation of various heavy metal ions in water.

[0031] In this invention, sulfonated polyethersulfone, as a polymeric framework material, not only possesses excellent chemical stability and mechanical strength, but its surface sulfonic acid groups (-SO3H) also provide negative charges, generating a strong electrostatic attraction to heavy metal cations. The ZIF-8 metal-organic framework material has a high specific surface area and a regular microporous structure, providing a large number of physical adsorption sites. At the same time, its zinc-imidazolium coordination structure forms Lewis acid sites, which can form strong coordination bonds with heavy metal ions. Cysteine-functionalized manganese ferrite nanoparticles provide thiol (-SH) coordination sites, exhibiting a strong affinity for heavy metal ions (especially mercury, lead, and cadmium), while also endowing the material with magnetism, facilitating rapid separation and recovery.

[0032] Example 1

[0033] A method for preparing an organic-inorganic hybrid material for removing heavy metal ions from wastewater includes the following steps:

[0034] Step 1, Preparation of sulfonated polyethersulfone:

[0035] 10 g of polyethersulfone (PES) was dissolved in 100 mL of N,N-dimethylformamide (DMF) and stirred at 60 °C until completely dissolved. Under ice bath conditions, 15 mL of concentrated sulfuric acid and 15 g of chlorosulfonic acid were mixed and stirred thoroughly, then slowly added to the PES solution. The reaction system was heated to 60 °C and reacted for 6 hours with stirring. Subsequently, the reaction solution was slowly poured into 500 mL of ice water, immediately producing a white precipitate. The precipitate was collected, washed repeatedly with deionized water until pH neutral, and finally dried under vacuum at 80 °C for 24 hours to obtain sulfonated polyethersulfone (SPES) with a sulfonation degree of 2.0 mmol / g.

[0036] Step 2, Synthesis of ZIF-8:

[0037] 2.92 g of zinc nitrate hexahydrate [Zn(NO3)2·6H2O] was dissolved in 100 mL of methanol to prepare a first solution; 6.48 g of 2-methylimidazole was dissolved in 100 mL of methanol to prepare a second solution. At room temperature, the first solution was rapidly poured into the second solution, and a white turbid liquid was immediately observed to form. The reaction was continuously stirred for 24 hours, followed by centrifugation (8000 rpm, 10 min). The precipitate was washed three times with fresh methanol to ensure complete removal of unreacted reactants. Finally, the product was vacuum dried at 60 °C for 12 hours to obtain white powdery ZIF-8 crystals with a specific surface area of ​​1500 m² / g and an average pore size of 1.2 nm.

[0038] Step 3, Preparation of manganese ferrite nanoparticles:

[0039] Under nitrogen protection, 1.98 g of manganese nitrate tetrahydrate [Mn(NO3)2·4H2O] and 8.08 g of ferric nitrate nonahydrate [Fe(NO3)3·9H2O] were dissolved in 200 mL of deionized water and stirred until completely dissolved. 50 mL of an aqueous solution containing 6 g of sodium hydroxide was slowly added dropwise while vigorous stirring, and a black precipitate was observed to form. Then, 2 g of polyvinylpyrrolidone (PVP, K-30) was added as a dispersant, and the reaction system was heated in an 80 °C water bath for 2 hours. After the reaction, the black product was separated using a permanent magnet and washed three times each with deionized water and ethanol to ensure complete removal of impurities. Finally, the product was vacuum dried at 60 °C for 12 hours to obtain black powdery manganese ferrite (MnFe2O4) nanoparticles with an average particle size of 35 nm and a saturation magnetization of 50 Å / g.

[0040] Step 4, L-cysteine ​​functionalization:

[0041] Two grams of the above-mentioned manganese ferrite nanoparticles were dispersed in 100 mL of phosphate buffered saline (PBS, pH=7.4) containing 2 grams of L-cysteine, and sonicated for 30 minutes to ensure complete dispersion. The reaction was then stirred at room temperature for 12 hours. During this time, L-cysteine ​​formed coordination bonds with the MnFe₂O₄ surface through its carboxyl group, while retaining the thiol group (-SH) as an active site. After the reaction, the product was separated using a permanent magnet, washed three times each with PBS buffer and deionized water, and finally vacuum dried at 40 °C for 12 hours to obtain functionalized MnFe₂O₄-Cys nanoparticles.

[0042] Step 5, Preparation of ternary composite materials:

[0043] 3 g of SPES was dissolved in 50 mL of DMF and stirred until completely dissolved. 3 g of ZIF-8 and 2 g of functionalized MnFe₂O₄-Cys nanoparticles were added to the solution and ultrasonically dispersed for 30 minutes to ensure uniform dispersion. The mixture was then stirred at room temperature for 6 hours to allow sufficient interaction between the three components. The mixture was poured into a flat mold and dried at 70 °C for 8 hours to form a composite membrane. The membrane was then immersed in deionized water for 24 hours to remove residual DMF solvent. Subsequently, it was vacuum dried at 40 °C for 24 hours. The dried composite membrane was pulverized and sieved to obtain particles of 0.5–1.0 mm, yielding the final ternary composite adsorbent material. In the obtained material, the mass percentages of SPES, ZIF-8, and MnFe₂O₄-Cys were 37.5%, 37.5%, and 25%, respectively.

[0044] Example 2

[0045] A method for preparing an organic-inorganic hybrid material for removing heavy metal ions from wastewater includes the following steps:

[0046] Step 1, Preparation of sulfonated polyethersulfone:

[0047] 8 g of polyethersulfone (PES) was dissolved in 80 mL of N,N-dimethylformamide (DMF) and stirred at 50 °C until completely dissolved. Under ice bath conditions, 12 mL of concentrated sulfuric acid and 12 g of chlorosulfonic acid were mixed and stirred thoroughly, then slowly added to the PES solution. The reaction system was heated to 50 °C and reacted for 4 hours with stirring. Subsequently, the reaction solution was slowly poured into 400 mL of ice water. The precipitate was collected, washed repeatedly with deionized water until pH neutral, and finally dried under vacuum at 80 °C for 24 hours to obtain sulfonated polyethersulfone (SPES) with a sulfonation degree of 1.5 mmol / g.

[0048] Step 2, Synthesis of ZIF-8:

[0049] 3.21 g of zinc nitrate hexahydrate was dissolved in 120 mL of methanol to prepare a first solution; 7.13 g of 2-methylimidazole was dissolved in 120 mL of methanol to prepare a second solution. The first solution was rapidly poured into the second solution at room temperature. The reaction was stirred continuously for 20 hours, followed by centrifugation to separate the products. The precipitate was washed three times with methanol and centrifuged. Finally, the product was vacuum dried at 60 °C for 12 hours to obtain ZIF-8 crystals with a specific surface area of ​​1200 m² / g and an average pore size of 1.0 nm.

[0050] Step 3, Preparation of manganese ferrite nanoparticles:

[0051] Under nitrogen protection, 2.18 g of manganese nitrate tetrahydrate and 8.89 g of ferric nitrate nonahydrate were dissolved in 220 mL of deionized water. 55 mL of an aqueous solution containing 6.6 g of sodium hydroxide was slowly added dropwise while vigorous stirring. 2.2 g of polyvinylpyrrolidone was added as a dispersant, and the reaction mixture was heated in a 90 °C water bath for 3 hours. After the reaction, the products were separated using a permanent magnet, washed three times each with deionized water and ethanol, and finally vacuum dried at 60 °C for 12 hours to obtain manganese ferrite nanoparticles with an average particle size of 20 nm and a saturation magnetization of 40 Å / g.

[0052] Step 4, L-cysteine ​​functionalization:

[0053] 2.2 g of manganese ferrite nanoparticles were dispersed in 110 mL of phosphate buffer solution (pH=7.2) containing 1.1 g of L-cysteine ​​and sonicated for 30 min. The mixture was then stirred at room temperature for 10 h. After the reaction, the product was separated using a permanent magnet, washed three times each with PBS buffer and deionized water, and finally vacuum dried at 40 °C for 12 h to obtain functionalized MnFe2O4-Cys nanoparticles.

[0054] Step 5, Preparation of ternary composite materials:

[0055] 2.4 g of SPES was dissolved in 40 mL of DMF. 3.6 g of ZIF-8 and 1.6 g of functionalized MnFe₂O₄-Cys nanoparticles were added to the solution and ultrasonically dispersed for 30 minutes. The mixture was then stirred at room temperature for 6 hours, poured into a flat mold, and dried at 70 °C for 8 hours to form a composite membrane. The membrane was immersed in deionized water for 24 hours, followed by vacuum drying at 40 °C for 24 hours. The dried composite membrane was pulverized and sieved to obtain particles of 0.5–1.0 mm, yielding the final ternary composite adsorbent material. The mass percentages of SPES, ZIF-8, and MnFe₂O₄-Cys in the obtained material were 30%, 45%, and 20%, respectively.

[0056] Example 3

[0057] A method for preparing an organic-inorganic hybrid material for removing heavy metal ions from wastewater includes the following steps:

[0058] Step 1, Preparation of sulfonated polyethersulfone:

[0059] 12 g of polyethersulfone (PES) was dissolved in 120 mL of N,N-dimethylformamide (DMF) and stirred at 70 °C until completely dissolved. Under ice bath conditions, 18 mL of concentrated sulfuric acid and 18 g of chlorosulfonic acid were mixed and stirred thoroughly, then slowly added to the above PES solution. The reaction system was heated to 70 °C and reacted for 8 hours, with stirring maintained throughout. Sulfonated polyethersulfone (SPES) with a degree of sulfonation of 2.5 mmol / g was obtained using conventional processing methods.

[0060] Step 2, Synthesis of ZIF-8:

[0061] Using a method similar to that in Example 1, but with the reaction time extended to 28 hours, ZIF-8 crystals with a specific surface area of ​​1800 m² / g and an average pore size of 1.5 nm were obtained.

[0062] Step 3, Preparation of manganese ferrite nanoparticles:

[0063] Under nitrogen protection, 1.78 g of manganese nitrate tetrahydrate and 7.27 g of ferric nitrate nonahydrate were dissolved in 180 mL of deionized water. Subsequent processing was carried out according to conventional methods, but the water bath temperature was reduced to 70 °C and the reaction time was shortened to 1 hour, yielding manganese ferrite nanoparticles with an average particle size of 50 nm and a saturation magnetization of 60 Å / g.

[0064] Step 4, L-cysteine ​​functionalization:

[0065] 1.8 g of manganese ferrite nanoparticles were dispersed in 90 mL of phosphate buffer solution (pH=7.6) containing 4.5 g of L-cysteine ​​and sonicated for 30 min. The mixture was then stirred at room temperature for 14 h, followed by conventional processing to obtain functionalized MnFe2O4-Cys nanoparticles.

[0066] Step 5, Preparation of ternary composite materials:

[0067] 3.6 g of SPES was dissolved in 60 mL of DMF. 2.7 g of ZIF-8 and 2.7 g of functionalized MnFe₂O₄-Cys nanoparticles were added to the solution, and subsequent processing was performed according to standard methods to obtain the final ternary composite adsorbent material. In the obtained material, the mass percentages of SPES, ZIF-8, and MnFe₂O₄-Cys were 40%, 30%, and 30%, respectively.

[0068] Example 4

[0069] A method for preparing an organic-inorganic hybrid material for removing heavy metal ions from wastewater is disclosed, employing a method similar to that in Example 1, but with the mass ratio of the three components adjusted in step five. In the resulting material, the mass percentages of SPES, ZIF-8, and MnFe2O4-Cys are 35%, 40%, and 25%, respectively.

[0070] Comparative Example 1

[0071] To verify the necessity of the ternary composite structure, a comparative material without ZIF-8 was prepared. A method similar to that used in Example 1 was employed, but in step five, only SPES and MnFe2O4-Cys components were used in a mass ratio of 60%:40%.

[0072] Comparative Example 2

[0073] To verify the necessity of the magnetic component, a comparative material without MnFe2O4-Cys was prepared. A method similar to that used in Example 1 was employed, but in step five, only SPES and ZIF-8 were used in a 50%:50% mass ratio.

[0074] Comparative Example 3

[0075] To verify the necessity of cysteine ​​functionalization, a comparative material using unfunctionalized MnFe2O4 nanoparticles was prepared. A method similar to that in Example 1 was used, but step four was omitted; the MnFe2O4 nanoparticles obtained in step three were directly mixed with other components. In the resulting material, the mass percentages of SPES, ZIF-8, and MnFe2O4 were 37.5%, 37.5%, and 25%, respectively.

[0076] Performance tests are as follows:

[0077] Test method:

[0078] Heavy metal adsorption capacity test: 0.1 g of adsorbent was added to 100 mL of a solution containing different initial concentrations (10-200 mg / L) of heavy metal ions (Pb²⁺, Cd²⁺, Cu²⁺, Zn²⁺), and stirred at 180 rpm for 6 hours at 25 °C to reach adsorption equilibrium. The adsorbent was separated using a permanent magnet, and the supernatant was taken. The concentration of residual heavy metal ions in the solution was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES, Thermo Scientific iCAP 7000). The equilibrium adsorption capacity was calculated according to formula (1):

[0079] q = (C0 - C ) × V / m (1)

[0080] Where, q To determine the equilibrium adsorption capacity (mg / g), C0 is the initial concentration (mg / L), and C... For equilibrium concentration (mg / L), V is the solution volume (L), and m is the adsorbent mass (g).

[0081] Effect of coexisting ions test: Different concentrations (0-6400 mg / L) of Na⁺, K⁺, Ca⁺ or Mg⁺ ions were added to a solution containing 50 mg / L Pb²⁺, and the adsorption amount was measured according to the method described above to evaluate the effect of coexisting ions.

[0082] Adsorption kinetics test: 0.1 g of adsorbent material was added to 100 mL of a solution containing 100 mg / L of heavy metal ions. The residual concentration was measured at different time points (5, 10, 20, 30, 60, 120, 240, 360 minutes) to study the adsorption kinetics characteristics.

[0083] Adsorbent regeneration performance test: A mixed solution of 0.1 mol / L hydrochloric acid and 0.05 mol / L EDTA was used as the desorbent to regenerate the adsorbed material. The adsorption capacity of the next cycle was measured after each regeneration to evaluate the recycling performance of the material.

[0084] Magnetic separation performance test: The adsorbed material is placed in an external magnetic field, and the time required for complete separation of the material is measured.

[0085] The test results are as follows:

[0086] Table 1. Maximum adsorption capacity of each example and comparative example for different heavy metal ions (unit: mg / g)

[0087] sample Pb²⁺ Cd²⁺ Cu²⁺ Zn²⁺ Example 1 195.3 142.8 108.5 92.7 Example 2 188.2 138.6 112.3 95.8 Example 3 192.5 145.1 104.2 88.4 Example 4 198.7 140.3 110.6 93.9 Comparative Example 1 103.5 75.2 62.1 55.8 Comparative Example 2 162.7 118.9 94.3 80.2 Comparative Example 3 147.8 92.4 85.6 73.5

[0088] As shown in Table 1, the ternary composite material of the present invention exhibits excellent adsorption performance for various heavy metal ions, especially for lead and cadmium ions, where the adsorption capacity reaches a very high level. In contrast, the adsorption capacity of Comparative Example 1 (without ZIF-8) is significantly reduced, demonstrating the important role of the ZIF-8 component in providing additional adsorption sites; Comparative Example 2 (without magnetic components) maintains good adsorption performance but lacks magnetic separation function; the adsorption performance of Comparative Example 3 (using unfunctionalized MnFe2O4) is significantly lower than that of the examples, indicating that the thiol group introduced by cysteine ​​functionalization makes an important contribution to enhancing the adsorption of heavy metal ions.

[0089] Table 2. Effect of coexisting ions on the adsorption of Pb²⁺ by the material in Example 1 (initial Pb²⁺ concentration 50 mg / L)

[0090] Coexisting ion concentration (mg / L) Adsorption rate (%) in the presence of Na⁺ Adsorption rate (%) in the presence of K⁺ Adsorption rate (%) in the presence of Ca²⁺ Adsorption rate (%) in the presence of Mg²⁺ 0 99.5 99.5 99.5 99.5 100 98.9 99.1 98.3 98.5 500 98.2 98.5 97.1 97.6 1000 97.6 97.9 95.8 96.2 2000 96.8 97.2 93.5 94.7 4000 95.3 95.8 91.2 92.5 6400 93.7 94.1 88.7 90.1

[0091] As shown in Table 2, even at coexisting ion concentrations as high as 6400 mg / L (equivalent to 128 times the Pb²⁺ concentration), the material of this invention still maintains a high lead ion adsorption rate, exhibiting excellent anti-interference ability. This is mainly attributed to the highly selective coordination of heavy metal ions by the thiol groups provided by cysteine ​​in the material.

[0092] Table 3. Recycling performance of materials in Example 1

[0093] Loop count Pb²⁺ adsorption capacity (mg / g) Pb²⁺ adsorption capacity retention rate (%) Cd²⁺ adsorption capacity (mg / g) Cd²⁺ adsorption capacity retention rate (%) 1 195.3 100 142.8 100 2 187.6 96.1 137.4 96.2 3 180.2 92.3 132.1 92.5 4 173.8 89 126.3 88.4 5 168.3 86.2 121.5 85.1

[0094] Table 3 shows that after five cycles of use, the adsorption capacity of the material for lead and cadmium ions remained above 85% of the initial value, demonstrating good regeneration performance and stability. This is mainly due to the material's excellent chemical stability and the synergistic effect of multiple adsorption mechanisms.

[0095] Table 4. Magnetic separation performance of materials in each embodiment.

[0096] sample Saturation magnetization (Å / g) Complete separation time (seconds) in 10 mL of solution Example 1 13.5 45 Example 2 8.9 68 Example 3 19.7 32 Example 4 14.2 43

[0097] Table 4 shows that all the materials in the examples exhibit good magnetic response performance and can be rapidly separated under the action of an external magnetic field, which greatly simplifies the post-processing process and avoids the cumbersome operation of traditional filtration and separation.

[0098] The excellent heavy metal adsorption performance of the organic-inorganic hybrid material of this invention is mainly attributed to the synergistic effect of the three components, which forms a multiple adsorption mechanism:

[0099] 1. Electrostatic adsorption mechanism: The sulfonic acid groups (-SO3H) on the surface of sulfonated polyethersulfone dissociate in aqueous solution, generating a negative charge, which attracts heavy metal cations in the water through electrostatic interaction. This mechanism is effective for all metal cations, but has low selectivity.

[0100] 2. Coordination Complexation Mechanism: The zinc-imidazolium coordination structure in ZIF-8 forms Lewis acidic sites, which can form coordinate bonds with the lone pairs of electrons of heavy metal ions. Simultaneously, the thiol group (-SH) in cysteine ​​has a strong affinity for heavy metal ions, especially soft acidic metal ions such as Pb²⁺, Cd²⁺, and Hg²⁺, forming stable metal-sulfur coordination bonds. This coordination complexation mechanism exhibits high selectivity and is key to the excellent performance of this material.

[0101] 3. Physical adsorption mechanism: The high specific surface area and regular microporous structure of ZIF-8 provide a large number of physical adsorption sites, which enhances the overall adsorption capacity of the material.

[0102] In practical applications, these three mechanisms work synergistically and complement each other, jointly improving the adsorption efficiency and selectivity of the material. Especially in complex aquatic environments, when the concentration of coexisting ions is high, the high selectivity of the coordination complexation mechanism ensures the preferential adsorption of target heavy metal ions by the material. Simultaneously, the magnetic properties provided by the manganese ferrite component allow the material to be rapidly separated by an external magnetic field, greatly simplifying the operation process and avoiding the risk of secondary pollution.

[0103] By comparing the performance of each embodiment, it can be determined that Example 4 provides the best overall performance, with the mass percentages of SPES, ZIF-8, and MnFe2O4-Cys being 35%, 40%, and 25%, respectively. This ratio ensures both high adsorption capacity (Pb²⁺ of 198.7 mg / g, the highest among all embodiments) and good magnetic response performance (complete separation time of 43 seconds). In this ratio, the relatively high ZIF-8 content provides more physical adsorption and coordination sites; the moderate MnFe2O4-Cys content ensures sufficient magnetic response performance and provides ample thiol coordination sites; and the balanced SPES content ensures the structural stability of the material and sufficient electrostatic adsorption sites.

[0104] The organic-inorganic hybrid material of the present invention can be widely used in the following fields:

[0105] 1. Industrial wastewater treatment: Suitable for treating wastewater containing heavy metals generated in industries such as electroplating, mining, metallurgy, and electronics, especially wastewater containing heavy metal ions such as lead, cadmium, copper, and zinc.

[0106] 2. Advanced drinking water treatment: It can be used to remove trace heavy metal pollutants from drinking water and ensure drinking water safety.

[0107] 3. Environmental remediation: It can be used for the remediation of polluted water bodies such as rivers and lakes, as well as the immobilization treatment of heavy metal pollution in soil.

[0108] 4. Precious metal recycling: It can be applied to the recovery of metals from wastewater containing precious metals, realizing resource reuse.

[0109] Compared with traditional adsorption materials, the material of this invention has the advantages of high adsorption capacity, good selectivity, easy separation and recovery, and recyclability, which not only have significant environmental benefits, but also good economic benefits.

[0110] This invention provides an organic-inorganic hybrid material for removing heavy metal ions from wastewater and its preparation method. Through the design of a ternary composite structure of sulfonated polyethersulfone / ZIF-8 / MnFe2O4, it integrates three mechanisms: electrostatic adsorption, coordination complexation, and physical adsorption, achieving highly efficient and selective adsorption of various heavy metal ions in water. The manganese ferrite magnetic component introduced into the material provides convenient magnetic separation capabilities, significantly simplifying the operation process and reducing the risk of secondary pollution. The thiol coordination sites introduced by cysteine ​​functionalization greatly enhance the material's affinity and selectivity for heavy metal ions. Experimental results show that this material exhibits excellent adsorption performance for heavy metal ions such as lead, cadmium, copper, and zinc, maintaining high selectivity even under high concentrations of coexisting ions, and possesses good regeneration performance and stability. This provides a new, efficient, economical, and environmentally friendly material for the treatment of heavy metal pollution in water bodies.

[0111] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of protection of the present invention.

Claims

1. An organic-inorganic hybrid material for removing heavy metal ions from wastewater, characterized in that, The material is a composite adsorbent material, composed of the following components by mass percentage: Sulfonated polyethersulfone, with a content of 30-40%; ZIF-8 metal-organic framework material, with a content of 30-45%; Cysteine-functionalized manganese ferrite nanoparticles, with a content of 20-30%; The sulfonated polyethersulfone forms a continuous phase matrix, and the ZIF-8 metal-organic framework material and the cysteine-functionalized manganese ferrite nanoparticles are dispersed as dispersed phases in the continuous phase matrix.

2. The organic-inorganic hybrid material according to claim 1, characterized in that, The degree of sulfonation of the sulfonated polyether sulfone is 1.5-2.5 mmol / g.

3. The organic-inorganic hybrid material according to claim 1, characterized in that, The ZIF-8 metal-organic framework material has a specific surface area of ​​1200-1800 m² / g and an average pore size of 1.0-1.5 nm.

4. The organic-inorganic hybrid material according to claim 1, characterized in that, The manganese ferrite nanoparticles have an average particle size of 20-50 nanometers and a saturation magnetization of 40-60 angstroms / gram.

5. A method for preparing the organic-inorganic hybrid material according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Prepare sulfonated polyethersulfone; Step 2: Synthesize ZIF-8 metal-organic framework material; Step 3: Prepare manganese ferrite nanoparticles; Step four: Perform L-cysteine ​​functionalization on the manganese ferrite nanoparticles; Step 5: The sulfonated polyethersulfone, the ZIF-8 metal-organic framework material, and the cysteine-functionalized manganese ferrite nanoparticles are mixed to prepare a ternary composite material.

6. The method according to claim 5, characterized in that, The preparation of sulfonated polyethersulfone in step one includes: dissolving polyethersulfone in N,N-dimethylformamide, adding a mixture of concentrated sulfuric acid and chlorosulfonic acid, reacting at 50-70°C for 4-8 hours, then pouring the reaction solution into ice water, collecting the precipitate and washing it with deionized water until neutral, and drying it under vacuum at 80°C for 24 hours.

7. The method according to claim 5, characterized in that, The synthesis of ZIF-8 in step two includes: dissolving zinc nitrate hexahydrate in methanol to form a first solution, dissolving 2-methylimidazole in methanol to form a second solution, quickly pouring the first solution into the second solution, stirring at room temperature for 20-28 hours, centrifuging to separate the product, washing with methanol three times, and drying under vacuum at 60°C for 12 hours.

8. The method according to claim 5, characterized in that, The preparation of manganese ferrite nanoparticles in step three includes: dissolving manganese nitrate tetrahydrate and ferric nitrate nonahydrate in deionized water at a molar ratio of 1:2, adding an aqueous solution containing sodium hydroxide under nitrogen protection, adding polyvinylpyrrolidone as a dispersant, heating the reaction in a water bath at 70-90°C for 1-3 hours, separating the product by magnetic force, washing it three times each with deionized water and ethanol, and vacuum drying it at 60°C for 12 hours.

9. The method according to claim 5, characterized in that, The L-cysteine ​​functionalization process in step four includes: dispersing the manganese ferrite nanoparticles in a phosphate buffer solution containing L-cysteine, wherein the pH of the phosphate buffer solution is 7.2-7.6; sonicating for 30 minutes; stirring at room temperature for 10-14 hours; magnetically separating the product; washing three times each with phosphate buffer and deionized water; and vacuum drying at 40°C for 12 hours.

10. The method according to claim 5, characterized in that, The preparation of the ternary composite material in step five includes: dissolving the sulfonated polyethersulfone in N,N-dimethylformamide, adding the ZIF-8 metal-organic framework material and the cysteine-functionalized manganese ferrite nanoparticles, ultrasonically dispersing for 30 minutes, stirring and mixing at room temperature for 6 hours, pouring the mixture into a flat mold, drying at 70°C for 8 hours to form a composite film, soaking in deionized water for 24 hours to remove the solvent, vacuum drying at 40°C for 24 hours, pulverizing the dried composite film and screening out particles of 0.5-1.0 mm to obtain the final composite adsorbent material.

Citation Information

Patent Citations

  • Hierarchical organic-inorganic hybrid adsorbents, their preparation methods and applications

    CN109046292B